Osteoporosis in the Jawbones: A Correlative Factor of Primary Trigeminal Neuralgia? - Liu, Li (International Scientific Literature, Inc., 2014)
Trigeminal neuralgia (TN), a neuropathic disorder of one or both of the trigeminal nerves, occurs most often in people over age 50. Extreme, sporadic, sudden burning or shock-like face pain in common activities greatly lowers quality of life. The precise cause of primary TN remains unknown, but it may be caused by vascular pressing on the trigeminal nerve in its root entry zone (REZ), demyelinization of trigeminal sensory fibers, or jawbone cavity. Accordingly, many treatments carry risks of adverse effects, recurrence, and complications. TN and osteoporosis have similar high-risk populations and a common influential factor – emotional stress – is also closed related to primary TN for calcitonin gene-related peptide and calcitonin. Jawbone cavity, which is a possible pathogenesis of TN, may be another form of jawbone osteoporosis. Therefore, we hypothesized that osteoporosis in jaws could be a correlative factor of primary TN. If this hypothesis is verified, it may suggest specific new ideas for the early preventive treatment of primary TN.